(untitled) (Research, Society and Development, 2021)
Mulberry (Morus spp.) is an evergreen tree belonging to the Moraceae family. The genus Morus has numerous described species, including Morus nigra, an important plant in agriculture and traditional cultures. The objective of this study was to conduct a scientometric research on the species M. nigra. Bibliographic data was been obtained from the Web of Science database considering two times periods. These analyzes showed that research involving M. nigra is concentrated in the areas of nutrition, pharmacology and agronomy science. Eastern countries and Brazil are the largest producers of knowledge about M. nigra. The research has shown different interests in recent decades, showing that the scientific knowledge produced about the species is associated with the objective for which the plant was used throughout history. There is a trend in the growth of publications focused on the potential antioxidant of M. nigra products. The articles had a greater impact factor in the past, however, a significant growth trend in research with M. nigra in the last three years, also suggested by the increase in the number of publications in the period. Understanding the publication standards assist in directing future research as well as in understanding the current panorama of research associated with the species.